The impact of the fourth wave of the COVID-19 pandemic on depression, anxiety and stress and related factors among medical students at Hue University of Medicine and Pharmacy - Tran, Nhu Minh Hang; Nguyen, Quang Ngoc Linh; Le, Tran Tuan Anh; Nguyen, Vu Quoc Huy (Tạp chí Y Dược Huế, 2025)
Background: Several studies have shown that the rates of mental health problems increased during the Coronavirus Disease 2019 (COVID-19) pandemic. Our research aimed to identify the prevalence and risk factors for depression, anxiety and stress among medical students at Hue University of Medicine and Pharmacy (HueUMP), Vietnam. Methods: A cross - sectional study included 2,350 medical students from the first year to the sixth year, in the 2021-2022 school year. We used the DASS-21 (Depression, Anxiety, Stress Scale-21 iterms) to assess depression, anxiety and stress in the participants; and to identify risk factors we used a self–designed questionnaire. Logistic regression was used to analyze factors associated with depression, anxiety and stress in medical students at Hue UMP. Results: The prevalence of depression, anxiety and stress among medical students during the 4th wave of the COVID-19 pandemic, as measured by the DASS- 21 scale was 38%, 33.2% and 17%, respectively. In multivariate regression analysis, stress-related factors included frequently feeling trapped during the period of social distancing/isolation, relationships affected or not maintained during the pandemic, parents and other family members getting unemployed. Factors associated with anxiety among participants included being female, having oneself or a family member(s) infected with Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2), constant worries about missing important scholarships or exams, frequent worries about online exams, feeling trapped due to social distancing/isolation, daily routines and relationships affected by the pandemic, and using beer, stimulants to relax. The factors related to depression in the study subjects included being female; being a 2nd, 3rd, or 6th- year student; having a family member(s) infected with SARS-CoV-2; feeling trapped due to social distancing/ isolation; having relationships affected by the Covid pandemic; not exercising regularly; and using alcohol/ beer/stimulants to relax. Conclusion: The rates of anxiety, depression, and stress among medical students ranged from 17% to 38%. Factors associated with these mental health problems included being female; being a 2nd, 3rd, or 6th-year student; pandemic-related factors and the students’ coping mechanisms.